Prevalence of human and non-human primate Plasmodium parasites in anopheline mosquitoes: a cross-sectional epidemiological study in Southern Vietnam - Vu Duc Chinh; Gaku Masuda; Vu Viet Hung; Hidekazu Takagi; Satoru Kawai; Takeshi Annoura; Yoshimasa Maeno (Tropical Medicine and Health, 2019)
Abstract Background Human malaria is a major threat in rural communities of central Vietnam. Anopheles dirus and Anopheles minimus species are critical malaria vectors in Vietnam, which transmit Plasmodium parasites. However, the entomological aspects of malaria transmission in some of the central provinces of Vietnam remain unexplored. Hence, a cross-sectional entomological survey was carried out to identify the malaria vector species and the transmission of Plasmodium parasites in seven endemic provinces of Vietnam. Methods Mosquitoes were collected from seven provinces, Gia Lai, Khanh Hoa, Phu Yen, Ninh Thuan, Binh Thuan, Dong Nai, and Binh Phuoc. The collection was conducted for four to eight consecutive nights using three established methods, indoor and outdoor human landing catches and light trap method. Nested-PCR analysis was performed to detect the Plasmodium species in the separated thorax and the abdomen of the individual mosquitoes. Results A total of 2278 mosquitoes belonging to one of the four species of anopheline mosquitoes, An. dirus, An. maculatus, An. aconitus, and An. minimus were collected. Among the collected mosquitoes, 1398 were analysed using nested-PCR, of which, 40 mosquitoes were positive for Plasmodium parasites. Most of these parasites were detected in the samples from the thorax region, followed by the abdominal portion. The parasites were detected in both the thorax and abdomen of An. dirus. Seven species of Plasmodium parasites were detected during the analysis, of which, Plasmodium inui was the most common species, followed by Plasmodium falciparum, Plasmodium vivax, Plasmodium cynomolgi, Plasmodium coatneyi, Plasmodium knowlesi, and Plasmodium fieldi. Out of the 49 positive samples, 12 showed mixed infections. Co-infection of P. inui with human and other non-human primate Plasmodium species was common. Conclusions This study demonstrated the presence of human and non-human primate Plasmodium infection in An. dirus, a predominant malarial vector. Further, we showed that An. ...